Assessing protected area effectiveness within the Caribbean under changing climate conditions: A case study of the small island, Trinidad. (February 2019) - Maharaj, Shobha S.; Asmath, Hamish; Ali, Safraz; Agard, John; Harris, Stephen A.; New, Mark
Highlights: Approximately 63% of the small island of Trinidad was found to be under forest. Most plantation forests for harvesting are located inside the protected areas (PAs). Almost 50% of climate space critical for conservation (CCS) is located outside PAs. PA effectiveness can be enhanced by maintaining forest cover in CCS outside of PAs. Regional Caribbean PA network can be a more effective way of controlling species loss. Abstract: Habitat loss and more recently, climate change are primary challenges to the effectiveness of protected area networks (PANs) in species conservation within many archipelagic biodiversity hotspots across the globe. An environmental niche model (ENM) of 11 high-conservation-value tree species was used to assess the effectiveness of the PAN within the Caribbean island of Trinidad under future (2050s) climate conditions. Overlay analyses were conducted inside and outside of existing PANs to determine the proportions of natural and plantation (monoculture) forests. Proportions of this species group's climate space projected to be critical for conservation (combination of stable and expanding zones or 'Z4') that are under forest cover were also calculated. Approximately 63% of Trinidad is forested, with the majority of plantation forests located within the PAN, producing noticeable areas of cleared forest when harvested. The ENM projected a drastic reduction in climate space for this group of high-conservation-value tree species across the island. However, approximately 54% of the Z4 space was projected to occur within the PAN; and 61% of the Z4 falling outside the PAN was under forest cover. Consequently, conservation of this species group could be greatly enhanced by increasing the proportion of its Z4 climate space outside the PAN under maintained forest/secondary vegetation cover. Given the small size of small island states (SIS) (such as those in the Caribbean) relative to the macro-scale of climate change, a more effective means of managing climate-induced species loss could involve the development of regional-scale PANs rather than separate efforts of individual SIS.